ANALISA FAKTOR PRILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI WILAYAH KERJA PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI TAHUN 2017 - Laily Husna (Universitas Batanghari Jambi, 2018)
One of methods to control the distribution of diseases is through effective preventive programs. The Clean and Healthy Living Behaviour (PHBS) is often used for preventive action by controlling the community behaviour to minimize the interaction between human and agents. The implementation of PHBS accounted for 43,40% in Province of Jambi. According to the data from Ministry of Health, thr national implementation of PHBS amongst household was 54,85% and 53,89% in 2010 and 2011 respectively. This research is an analytical study using cross sectional design. Thr study aims to identify determinant factors associated with community behaviour. Analytical survey refers to a study which deeply explore how and why the health phenomenon occurs. This is later analysed using correlation and phenomenon dynamic analysis. The research indicates that there is no significant correlation among educational degree, income, family member, knowledge and attitude towards clean and healthy living behavior. After conducting the test, however, the educational degree, income, family members, and attitute are indicated as counfounding factors. It is recommended that inter sectoral collaborative works are essentially required in order to develop community empowernment, particularly using media and participatory action method to apply healthy behaviour. Keyword: Factor Analysis, The Clean and Healthy Living Behaviour